Introduction to Electrodynamics - David J. Griffiths (New Delhi Cambridge University Press, 2017)
School of Mathematics and Natural Science
MIR No: 178
Order Date: 2024-09-09
Order No: CU/OPEX/LIBRARY/33/2024-25
Received Date: 2024-01-10
Keywords: Physics, ElectroDyanmics